Facial emotion detection using GPSO and Lucas-Kanade algorithms - Bashir, Mohammed Ghandi; Nagarajan, Ramachandran, Prof. Dr.; Hazry, Desa, Prof. Madya Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/